2017
DOI: 10.1177/1403494817735755
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes of sick leave due to mental disorders: A prospective study of discordant twin pairs

Abstract: Sick leave due to mental disorders increased the risk of reoccurring sick-leave within two years, disability pension and unemployment, independent of genetics and shared environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 119 publications
(222 reference statements)
0
15
0
Order By: Relevance
“…Hence, there is a possibility that familial factors influence the associations between CWP and CMDs with future SA and DP. To our knowledge, few studies have had access to twin data to examine adverse outomes of CWP and CMDs among individuals with a history of SA [18]. By studying twins that share 50-100% of their genetic material and rearing environment a possibility is provided to adjust for those unmeasured factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a possibility that familial factors influence the associations between CWP and CMDs with future SA and DP. To our knowledge, few studies have had access to twin data to examine adverse outomes of CWP and CMDs among individuals with a history of SA [18]. By studying twins that share 50-100% of their genetic material and rearing environment a possibility is provided to adjust for those unmeasured factors.…”
Section: Introductionmentioning
confidence: 99%
“…There are several indicators which would support such a stance; for example, evidence-based recommendations for common back pain emphasize the importance of maintaining normal activities, including gainful work, to lower the risk of disability [17]. For Common Mental Disorders (CMDs) the importance of returning to work despite remaining psychological symptoms is also considered as crucial to avoid negative long-term effects such as prolonged sick leave, unemployment, social isolation and financial problems [18][19][20]. However, the availability of resources and support at work can be expected to be of vital importance when an employee who does not feel well goes to work [18,19] To the best of the authors' knowledge there exists no published comprehensive longitudinal study of the potential moderating impact of psychosocial job resources on the relation between presenteeism and health.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, some indications exist that severity of the depression or an adverse effect of the sick leave itself may also play a role in the association between sick leave and mortality. In a previous twin study, we found that the increased risk of subsequent sick leave, unemployment and disability pension was independent of familial factors [9]. Another twin study that investigated the influence of familial factors on the association between sick leave, all causes, and mortality found only minimal influence [24].…”
Section: Introductionmentioning
confidence: 76%
“…Sick leave due to mental disorders has been found to have a negative effect on future work life, such as a higher risk of unemployment and a lower income [7][8][9]. Sick leave has also been associated with a number of adverse health outcomes, such as poor self-rated health [10,11] and early death [12].…”
Section: Introductionmentioning
confidence: 99%